What else should I read? : guiding kids to good books : volume 2 - Berman, Matt. (Englewood, Colo. : Libraries Unlimited, 1996)
Contains topic webs for thirty great works of children's literature, directing readers to other books with similar themes. Lists of books are designed to be reproduced on bookmarks.
Includes bibliographical references and indexes.
Kirkus Review.
Library Talk.
Professional
Keywords: Children's stories -- Bibliography; Children -- United States -- Books and reading; Children's literature -- Bibliography; Children -- United States -- Books and reading